Antibody and TLR7 agonist delay viral rebound in SHIV-infected monkeys. (15th November 2018) - Borducchi, Erica; Liu, Jinyan; Nkolola, Joseph; Cadena, Anthony; Yu, Wen-Han; Fischinger, Stephanie; Broge, Thomas; Abbink, Peter; Mercado, Noe; Chandrashekar, Abishek; Jetton, David; Peter, Lauren; et al.
Abstract The latent viral reservoir is the critical barrier for the development of a cure for HIV-1 infection. Previous studies have shown direct antiviral activity of potent HIV-1 Env-specific broadly neutralizing antibodies (bNAbs) administered when antiretroviral therapy (ART) was discontinued, but it remains unclear whether bNAbs can target the viral reservoir during ART. Here we show that administration of the V3 glycan-dependent bNAb PGT121 together with the Toll-like receptor 7 (TLR7) agonist vesatolimod (GS-9620) during ART delayed viral rebound following discontinuation of ART in simian–human immunodeficiency virus (SHIV)-SF162P3-infected rhesus monkeys in which ART was initiated during early acute infection. Moreover, in the subset of monkeys that were treated with both PGT121 and GS-9620 and that did not show viral rebound after discontinuation of ART, adoptive transfer studies and CD8-depletion studies also did not reveal virus. These data demonstrate the potential of bNAb administration together with innate immune stimulation as a possible strategy for targeting the viral reservoir. In monkeys infected with an AIDS-like virus, a combination of a broadly neutralizing antibody and an immune stimulator during antiretroviral therapy suppressed viral rebound after antiretroviral drug discontinuation.